Pemanfaatan Umbi-Umbian sebagai Bahan Pengisi dalam Pengembangan Pakan Ikan Berbasis Nutrisi Alami: Utilization of Tubers as Filler Ingredients in the Development of Natural Nutrition-Based Fish Feed - Kiki Haetami; Yoga Nugraha Budiana; Abun Abun (PharmaCine : Journal of Pharmacy, Medical and Health Science, 2025)
Freshwater fish feeds are typically high in protein (>25%), creating a need for cost-effective carbohydrate fillers that do not compromise growth performance. Tuber crops (cassava, taro, sweet potato, potato) are promising carbohydrate sources; however, antinutritional factors and processing methods largely determine their success. This review searched literature on Google Scholar. Inclusion criteria were studies on aquaculture fish species that reported at least one performance outcome (growth/SGR, FCR, PER) or digestibility, and that specified the tuber organ/material and the applied processing. Exclusion criteria were non-aquatic studies, studies without performance/digestibility data, and non-scholarly secondary sources. Two reviewers screened independently, with disagreements resolved by consensus. A narrative/thematic synthesis was conducted. Fermentation and/or heat processing consistently reduced antinutritional factors and improved starch digestibility. In tilapia and catfish, carbohydrate substitution from tubers was generally safe at ~20–30% of diet carbohydrates without significant deterioration in SGR/FCR when adequate processing was applied; higher inclusion levels depend on species, life stage, and detoxification intensity. Tuber crops are therefore promising filler ingredients, particularly when preceded by fermentation. Practically, a 20–30% substitution can serve as a starting point for formulation, followed by optimization by species and production stage. Keywords: Tuber crops; Filler materials; Spare protein; Processing; Aquaculture.